Cervical cancer preventive practice trend according to area of ​​residence of women of childbearing age, 2013 to 2020 - Chafloque-Chavesta, Jhonny Jesus (2021)
Introduction: The Papanicolaou examination is a screening method, whose performance and collection of results, allow the prevention, detection and timely treatment of cervical lesions, which through a slow and progressive evolution can become cervical cancer . Objective: Describe the trend of cervical cancer preventive practices according to area of ​​residence of women of childbearing age, 2013 to 2020. Materials and Methods: Observational and retrospective study of analysis of secondary sources, based on the Demographic and Family Health Survey (ENDES ) from 2013 to 2020, in which women between the ages of 15 and 49 were evaluated. The study variables were the Papanicolaou screening and the collection of results. Stratifications, weights and trend line graphs were used in the analysis. Results: The highest percentage of women who underwent the Papanicolaou was 85.2% (CI 83.7% -86.5%; CV 0.009) in 2017. Regarding the collection of Papanicolaou results, the highest percentage was 83.4% (CI 81.4% -85.3%; CV 0.012) in 2020. The weighted count of women who underwent this screening increased by 61.6% (57.8% - 65.2%; CV 0.03) to 64.5% (62.9% -66%; CV 0.012) during the study period, while in rural areas, it decreased from 16.5% (14 % -19.4%; CV 0.082) to 16% (15.1% -17%; CV 0.029) (Graph N ° 1). Meanwhile, the collection of results increased from 63.9% (59.3% -68.3%; CV 0.036) to 69.9% (67.3% -72.5%; CV 0.019) in the urban area and there was a reduction from 14.3% (11.6% -17.5%; CV 0.104) to 13.5% (11.9% -15.3%; CV 0.065) in rural areas. Conclusions: Cervical cancer preventive practices, such as taking Papanicolaou and collecting results, have maintained similar percentages during the study period, in rural and urban areas.